Synthesis, Cytotoxicity and Molecular Docking Simulation of Novel bis-1,4-Dihydropyridines Linked to Aliphatic or Arene Core via Amide or Ester-Amide Linkages - Abdella, Amna M.; Abdelmoniem, Amr M.; Ibrahim, Nada S.; El-Hallouty, Salwa M.; Abdelhamid, Ismail A.; Elwahy, Ahmed H.M. (Mini Reviews in Medicinal Chemistry, 2020)
Objective: Novel bis(1,4-dihydropyridine-3,5-dicarbonitrile) derivatives linked to aliphatic or aromatic cores via amide or ester-amide linkages were prepared and their structures were confirmed by several spectral tools. Methods: The synthesis of novel N,N'-(alkanediyl)bis(2-(2-(3,5-dicyano-2,6-dimethyl-1,4-dihydropyridin- 4-yl)phenoxy)acetamide) by acid-catalyzed condensation of the bis-aldehydes with four equivalents of 3-aminocrotononitrile was reported. Results: The structures of the synthesized compounds were confirmed by different spectral tools. The molecular docking stimulation studies indicated that the prepared compounds bind to the active site of cellular inhibitor apoptotic protein (cIAP1-BIR3). MTT assay for the novel bis(1,4-dihydropyridines) was performed on two different human cell lines (A549 and HCT116). Conclusion: Compound 5a showed higher cytotoxic activity against A549. Compound 5d showed moderate activity against HCT116. The rest of compounds indicated lower or no activity against both cell lines.
Keywords: 3-Aminocrotononitrile